Platinum-nickel catalyst: The effect of promoters in cis-oleic acid adsorption - Simonetti, Sandra Isabel (2013)
The study of the cis-oleic acid adsorption, on clean and promoted (K, Mg, Co, B or Pd) PtNi(1 1 1) surface was performed by quatum chemical calculations. The oleic acid adsorption on PtNi(1 1 1) surface shows a weak molecule–surface interaction. No preferential site for C C adsorption is computed and only the C O adsorption is favored on the clean PtNi(1 1 1) surface. The adsorption properties of the PtNi(1 1 1) are improved by promoters. The stability of the system is increased and the C C/surface distances are reduced when promoters are present. Among the considered promoters, Co has the best performance in terms of system stability. The lowest C p orbital substantially interacts with Pt and Co s, p and d orbitals. The change electron density of metal centers, enhance the C C adsorption being the Pt–C interaction the more favored. After adsorption, the strength of the C C, Pt Pt and Pt Co bonds decrease while a molecule–surface bond is formed.